A Body of Longing: The Erotic and Decolonial Power of the Biotext - Fernando, Tarini Nandita (Arts, 2023)
A Body of Longing: The Erotic and Decolonial Power of the Biotext is a creative thesis that explores the radical potential of the biotext as a genre that defies formal and generic restrictions, especially the expectations of autobiography. Using postcolonial, affective, and literary deconstructionist theories, I explore questions such as, how does the biotext challenge formal and generic categorization? What decolonial and feminist potentials lie in the rejection of literary categories by Black, Indigenous, and writers of colour in a settler-colonial state? I investigate these questions through close analyses of experimental biotextual writings in contemporary Canadian and Indigenous English-language literatures, such as Fred Wah’s Diamond Grill, Jordan Abel’s NISHGA, and, of course, my own biotextual poetry. Through my analyses, I find that the biotext, through its lack of strict generic and formal expectations, inherently encourages experimentation and the blurring of literary categories. This rejection of categorization is what allows BIPOC authors to resist readability by the Canadian state, which seeks to fetishize and restrict their stories within the colonial borders of the nation-state. In investigating the work of authors like Wah, I also theorize that one reason diasporic Asian-Canadian writers have been so foundational to the history of the biotext is that they are particularly well-positioned to use formal and generic experimentation to challenge constructions of home and identity. I also argue that visual experimentation is a key tool that heightens the decolonial breaking of generic and formal boundaries that I attempt in my poetry. Drawing strongly from Audre Lorde’s theory of the power of the erotic, my poetry collection takes up the genre of biotext and articulates my own vision for erotic, decolonial, Sri Lankan, feminist futures. Inspired by Abel’s oeuvre, M. NourbeSe Philip’s Zong!, and Joshua Whitehead’s full-metal Indigiqueer, my poetry makes intentional use of visual experimentation to ...